Potential clinical application of masseter and temporal muscle massage treatment using an oral rehabilitation robot in temporomandibular disorder patients with myofascial pain. Issue 4 (4th July 2015) - Ariji, Yoshiko; Nakayama, Miwa; Nishiyama, Wataru; Ogi, Nobumi; Sakuma, Shigemitsu; Katsumata, Akitoshi; Kurita, Kenichi; Ariji, Eiichiro
Abstract : Objectives: To investigate the safety, suitable treatment regimen, and efficacy of masseter and temporal muscle massage treatment using an oral rehabilitation robot. Methods: Forty-one temporomandibular disorder (TMD) patients with myofascial pain (8 men, 33 women, median age: 46 years) were enrolled. The safety, suitable massage regimen, and efficacy of this treatment were investigated. Changes in masseter muscle thickness were evaluated on sonograms. Results: No adverse events occurred with any of the treatment sessions. Suitable massage was at pressure of 10 N for 16 minutes. Five sessions were performed every 2 weeks. Total duration of treatment was 9·5 weeks in median. Massage treatment was effective in 70·3% of patients. Masseter muscle thickness decreased with treatment in the therapy-effective group. Conclusion: This study confirmed the safety of massage treatment, and established a suitable regimen. Massage was effective in 70·3% of patients and appeared to have a potential as one of the effective treatments for myofascial pain.